Clinical Recommendations of the Russian Gastroenterological Association and Association of Coloproctologists of Russia on Diagnosis and Treatment of Constipation in Adults - V. T. Ivashkin; Yu. A. Shelygin; I. V. Maev; A. A. Sheptulin; D. V. Aleshin; S. I. Achkasov; E. K. Baranskaya; N. D. Kulikova; T. L. Lapina; A. I. Moskalev; M. F. Osipenko; E. A. Poluektova; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Current clinical recommendations are intended to supply gastroenterologists, physicians and general practitioners with modern methods for the diagnosis and treatment of constipation.Key points. Constipation is deﬁned as primary (functional) and secondary form, the latter comprising a manifestation of another illness. The causes of constipation are diagnosed with colonoscopy, especially in patients aged over 50 having “anxiety symptoms” and hereditary colorectal oncological predisposition. Indications may also include the bowel transit time estimation with radiopaque markers, balloon expulsion test, anorectal manometry, defecography and electromyography. Therapy for constipation should be comprehensive and concern lifestyle, diet recommendations and use of medications (psyllium, macrogol, lactulose, lactitol, contact laxatives, prucalopride). Patients with a less eﬀective conservative therapy and largely reduced quality of life should be considered for surgical intervention.Conclusion. An eﬀective therapy for constipation requires a correct diagnosis of its causes.